Management of total entrepreneurial activity by adaptive neuro-fuzzy technique - Janković, Vučina; Jović, Srđaj; Đokić, Jelena (Journal of Production Engineering, 2018)
Adaptive neuro fuzzy network or ANFIS could be used for different aspects of prediction during productive development. In this study ANFIS network was appliced for prediction of bending and thickness of shaped surface by laser formation. Laser manufacturing represent imporant part in new productive development. Shaped surface modeling by laser forming process needs many irradiations along surface paths with different parameters of heating. This surface requires thickening and bending in order to get required shapes. In this study was attempted to analyze the process parameters influence on the bending and thickening of the shaped surface by laser. The used inputs were circular and radial laser scan, laser spot diameter, laser power and scan speed. The selection procedure can produce results to simplify the shaped surface forming. Finally it was attamted to determine how services as added values have infleunce on the enterpreneusthip activity for laser manufacturing business.